(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
One of the current problems in the world is the high level of the underground economy. The process that remains problematic is to determine the level of the hidden economy. By determining the determinants of the hidden economy and formulating a specific policy related to them, it is possible to reduce the level of its growth, but it is impossible to completely exclude it from the economy. In this case will be data from 1991-2015used. In the article, a statistical analysis of the factors affecting the level of the hidden economy of Asian countries was carried out. It includes 12 key determinants such as GDP per capita, tax revenue, unemployment rate, trade openness, GDP per capita growth, Doing Business rating, percentage of people using the Internet, inflation rate, political stability, government efficiency, rule of law, and corruption management.